O idoso e a praia: revelando significados - Oliveira, Ana Luiza Teixeira de (2008)
The present study was carried out in the city of Santos-SP (Brazil) with the aim of understanding the meaning of the term beach environment for elderly individuals who regularly attend this natural space for the performance of physical activities. This qualitative study, supported by the gerontology literature, employed the methodological resources of the analysis of oral reports and observations of activities developed by a group of elderly individuals. Volunteers were selected to participate in the study: five men (average age of 71.8 years) and five women (average age of 75.4 years). Socioeconomic data were collected using a questionnaire with closed questions. An open interview with a dialogue nature was then conducted. Data on information from the questionnaire were organized in a databank and later structured in the form of tables to facilitate the reader s understanding. Interviews were recorded on an audio recorder and in a field log; the topics were categorized in order for readers to be able to navigate better. Topics included the body that ages and the body that moves; beach environment; reflections on the body-nature relationship; body techniques; topophilia, health in the normal and pathological realms in the ageing process; as well as topics such as recreation and the history of the city of Santos